Citrus Aromatherapy as Complementary Medicine for Pain Management - Karolin Adhisty (Arkus, 2017)
Pain is an unpleasant sensory sensation that can coincide with the onset of the disease. This pain will cause a psychological condition that will disrupt the patient's daily life if it is not treated immediately. Health workers will certainly provide interventions that patients and their families can use to support this reduction in sensation. A complementary action that can be used to reduce this pain perception is citrus aromatherapy. Citrus aromatherapy has a complete content not only relaxes the mind but also inhibits pain inhibitors so that the perception of pain can be immediately reduced. The pain decrease perception will undoubtedly improve patients' quality of life after the disease, both acute and chronic.